2020
DOI: 10.1186/s12864-020-07176-8
|View full text |Cite
|
Sign up to set email alerts
|

Extensive gene rearrangements in the mitogenomes of congeneric annelid species and insights on the evolutionary history of the genus Ophryotrocha

Abstract: Background Annelids are one the most speciose and ecologically diverse groups of metazoans. Although a significant effort has been recently invested in sequencing genomes of a wide array of metazoans, many orders and families within the phylum Annelida are still represented by a single specimen of a single species. The genus of interstitial annelids Ophryotrocha (Dorvilleidae, Errantia, Annelida) is among these neglected groups, despite its extensive use as model organism in numerous studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 101 publications
(116 reference statements)
1
13
1
Order By: Relevance
“…elegans conform to this putative Polynoidae ground pattern (Fig. 1 b), and to a large extent, so does G. jameensis, differing only by the position of two tRNAs, which are generally more labile 34 . Similarly, this Polynoidae ground pattern was also found in the polynoid Polyeunoa laevis McIntosh, 1885, adding validity to the idea of a conserved gene order ground pattern in Polynoidae 35 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…elegans conform to this putative Polynoidae ground pattern (Fig. 1 b), and to a large extent, so does G. jameensis, differing only by the position of two tRNAs, which are generally more labile 34 . Similarly, this Polynoidae ground pattern was also found in the polynoid Polyeunoa laevis McIntosh, 1885, adding validity to the idea of a conserved gene order ground pattern in Polynoidae 35 .…”
Section: Discussionmentioning
confidence: 72%
“…In Annelida, this speculation has led to the suggestion of a common ground pattern across Errantia and Sedentaria 30 32 . However, recent increases in mitogenome sampling across phyllodocid lineages (i.e., Syllidae, Aphroditiformia) showed that mitochondrial gene orders are more variable than previously anticipated 25 , 30 , 33 , 34 . In Aphroditiformia, Zhang et al 25 recovered six different mitochondrial gene orders from their sampling of 16 scale worms, four being from within Polynoidae.…”
Section: Discussionmentioning
confidence: 87%
“…The level of gene order rearrangement in mitogenomes differs among animal groups. For example, the gene order of annelids shows considerable variation even within a single genus (Tempestini et al, 2020; Sun et al, 2021), whereas brachyurans show relatively stable arrangements that are shared among families (Tan et al, 2018). The gene order of Thoracotremata in a single family is often the same with some exceptions, such as Dotillidae (three dotillids in Kobayashi et al, 2021), Pinnotheridae (six pinnotherids in Sun et al, 2022), and Xenograpsidae (two xenograpsids in Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The gene order of a mitogenome is relatively conserved; the order is sometimes the same among higher taxa, e.g., across orders of annelids, when considering only protein-coding genes (PCGs) 3 . Conversely, the gene order in some marine invertebrates, including annelids, shows an intra-familial variation 2 , 5 9 and may shed light on the phylogenetic relationships of relatively closely related taxa.…”
Section: Introductionmentioning
confidence: 99%